Measuring the Post-Impact of Programming MOOCs: Development and Validation of an Instrument - Merilin Säde; Reelika Suviste; Piret Luik (MDPI AG, 2021)
Massive open online courses (MOOCs) can potentially affect the lives of millions of people, but there is little research on how a programming MOOC could affect participants' lives after participation. In Estonia, we have organised several programming MOOCs over the years, attended by over 14,000 people. This inspired us to develop and validate a scale for measuring the impact of programming MOOC on participants' lives. We analysed data from 1261 MOOC participants who had completed at least one of our programming MOOCs. Confirmatory factor analysis (CFA) was used to validate the developed scale. The final model fitted quite well to the data. We found that the factors that influence learners' lives after a MOOC include acquired learning skills, interest in continuing computer science related studies, learning experience gained from the MOOC, the MOOC's impact on work and personal life, and new contacts that are established with other participants and organisers. We also compared the means of the factors. The highest-rated factor was related to the learning experience from the MOOC and the lowest-rated was related to finding new contacts through the MOOC.